2011
DOI: 10.1103/physrevb.83.224505
|View full text |Cite
|
Sign up to set email alerts
|

Doping dependence of the Nernst effect in Eu(Fe1xCox)

Abstract: We report a systematic study of the transport properties in the series of Eu(Fe 1−x Co x ) 2 As 2 single crystals with x = 0, 0.15, 0.20, and 0.30. Spin-density-wave (SDW) order is observed in the undoped and the least doped samples with x = 0 and 0.15 at T SDW = 191 and 131 K, respectively. For x = 0.15 and 0.20 Eu(Fe 1−x Co x ) 2 As 2 becomes a superconductor with T onset c = 20.5 and 8.5 K, respectively. We find properties of the SDW state in the parent EuFe 2 As 2 compound well described by the Dirac-fermi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
44
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 30 publications
5
44
2
Order By: Relevance
“…The additional correlation with the critical fluctuations observed by S/T in the same compound supports the argument of this paper [28]. A Nernst effect study on a similar compound Eu(Fe 1−x Co x ) 2 As 2 showed the existence of an anomalous contribution that peaks above T c (around 40K) in the sample where SDW and SC coexist [77]. The authors there associated this contribution with the Fermi-surface reconstruction caused by spin fluctuations.…”
Section: S/t -Quantum Criticality and Superconductivitysupporting
confidence: 69%
“…The additional correlation with the critical fluctuations observed by S/T in the same compound supports the argument of this paper [28]. A Nernst effect study on a similar compound Eu(Fe 1−x Co x ) 2 As 2 showed the existence of an anomalous contribution that peaks above T c (around 40K) in the sample where SDW and SC coexist [77]. The authors there associated this contribution with the Fermi-surface reconstruction caused by spin fluctuations.…”
Section: S/t -Quantum Criticality and Superconductivitysupporting
confidence: 69%
“…17,18 To the best of our knowledge, so far the zero-resistivity state in Eu(Fe 1−x Co x ) 2 As 2 was only realized in the single crystals grown using Sn as the flux, but with relatively lower superconducting transition temperature (T sc ∼ 10 K). [19][20][21][22] In addition, the SDW order in the self-flux-grown crystals was found to be suppressed much faster upon Co doping than that in the Sn-flux-grown crystals. 17,20 It is quite clear that the physical properties of the Eu(Fe 1−x Co x ) 2 As 2 single crystals strongly depend on the growth techniques.…”
Section: Introductionmentioning
confidence: 91%
“…In a pioneering study Zhu et al reported an anomalous suppression of the off-diagonal thermoelectric current in optimally doped LaFeAsO 1−x F x and suggested the presence of SDW fluctuations near the superconducting transition [19]. Matusiak et al observed a strong enhancement of the Nernst coefficient in the SDW state of the parent compounds and at low doping levels of CaFe 2−x Co x As 2 and EuFe 2−x Co x As 2 , but did not find any particular anomaly in the Nernst effect of a purely superconducting doping level that could be attributed to neither vortex flow nor to SDW fluctuations [20,21]. Kondrat et al systematically investigated the doping-evolution of the Nernst effect in LaFeAsO 1−x F x [13].…”
Section: Introductionmentioning
confidence: 99%